Temperatura e pressão na cinética de hidratação em feijões adzuki e mungo - Pramiu, Pétterson Vinícius (2024)
Several bean varieties have been essential components to the diet of hundreds of millions of people worldwide due to their high nutritional value. Thus, hydration is an important phase during the processing of adzuki and mung beans, in which the product absorbs water for germination, fermentation, or cooking. In industrial applications, grains with higher water absorption capacity are preferred, as they require less energy for treatments and result in a final product with higher quality. So, in this research, it was studied the influence of temperature and pressure on hydration kinetics of these two bean varieties. Hydration kinetics was evaluated according to the variation in moisture content within the grains throughout this process. The mathematical modeling of hydration kinetics in adzuki and mung beans was evaluated by models shown by Abu-Ghannam (1998), Peleg (1988), Kaptso et al. (2008), and Ibarz and Augusto (2015). Kinetic parameters of these models were estimated using non-linear regression adjustment of these models to the experimental moisture content variation data. The effects of temperature and pressure were observed considering variation in kinetic parameters present in these models. Subsequently, an expression was found out to associate these parameters to temperature and pressure, using a second-order response surface model. These kinetic parameters were also related considering the combined effect of temperature and pressure during hydration by an Arrhenius-Eyring type constitutive relationship. Moisture content variation data for these beans have a sigmoidal behavior, and models by Kaptso et al. (2008) and Ibarz and Augusto (2015) have provided the best adjust to the obtained data.